2021
DOI: 10.18502/fem.v6i1.7675
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 related hospitalization costs; assessment of influencing factors

Abstract: Objective: Our aim is to assess the effective factors on hospitalization costs of COVID-19 patients. Methods: Data related to clinical characteristics and cost of hospitalized COVID-19 patients from February 2020 until July 2020, in a public teaching hospital in Tehran, Iran was gathered in a retrospective cohort study. The corresponding factors influencing the diagnostic and therapeutic costs were evaluated, using a generalized linear model. Results: The median COVID-19 related diagnostic and ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Our study showed that diabetes was not related to the median of hospitalization costs in both groups that is opposite to Ohsfeldt et al study [ 15 ]. Regarding other comorbidities, suffering from cardiovascular disease as a risk factor for the disease severity and death [ 13 ] increased the median cost in both groups that is in line to another study in Iran [ 8 ].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Our study showed that diabetes was not related to the median of hospitalization costs in both groups that is opposite to Ohsfeldt et al study [ 15 ]. Regarding other comorbidities, suffering from cardiovascular disease as a risk factor for the disease severity and death [ 13 ] increased the median cost in both groups that is in line to another study in Iran [ 8 ].…”
Section: Discussionsupporting
confidence: 80%
“…Disease severity and prolonged hospitalization could be related with higher cost in patients. Studies have shown that the hospitalization costs in the COVID-19 patients are different based on different characteristics across countries [ 2 , 7 , 8 ]. Planning for and forecasting the future needs to the financial support especially for the fragile population could empower countries in the management and control of the future crisis caused by the next wave of COVID-19 pandemic [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, studies from Kenia and Myanmar have used market prices to report costs [ 15 , 35 ]. Studies from Saudi Arabia and Iran, on the other hand, have used medical tariffs to report costs, and a study from Ethiopia has used medical documents in public health centers to report diagnostic costs [ 24 , 27 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data on costs are presented as mean per patient, except for HajiAghajani et al (2022), presented as median cost per patient.…”
mentioning
confidence: 99%